SOSIALISASI LATIHAN KEGEL TERHADAP INKONTINENSIA URINE PADA LANJUT USIA DI DESA SIDODADI KECAMATAN BERINGIN - Arfah May Syara; Rahmad Gurusinga; Anita Sri Gandaria Purba; Winda Ardyana Hutagaol; Fadlilah Widyaningsih (JURNAL PENGMAS KESTRA (JPK), 2021)
Kegel exercises are exercises that are used to strengthen the pelvic floor muscles by contracting the rectum and urethra which are held for 3-5 seconds and then relaxing them, weakened pelvic floor muscle contractions can cause urinary incontinence, which is one of the problems experienced by the elderly and needs to be done. get special attention along with the increasing elderly population in Indonesia. The purpose of this community service was to determine the effect of Kegel exercises on the frequency of urinary incontinence in the elderly. This community service socialization was carried out to 38 elderly people in Sidodadi Village, Beringin District. The results of this community service show that after doing Kegel exercises there is a 2.5% decrease in urinary incontinence frequency with a p value = 0.001, so that there is an effect of giving Kegel exercises on urinary incontinence. The results of this study indicate the need for regular Kegel exercises and it is hoped that health workers in the area will be able to apply Kegel exercises with the elderly on a regular basis. By doing Kegel exercises, it can provide exercise to the pelvic muscles related to the regulation of the urinary system in regulating the urinary process in the elderly. Elderly people and their families should be able to do Kegel exercises as an alternative to non-pharmacological techniques that are easy to do without harmful effects in providing intervention and prevention in the elderly who experience urinary incontinence.